Enhancing Mental Health Education and Foreign Language Skills in Sports School Students: An Integrated Approach - Xi Pei; Shixue Gong; Baitao Liu, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Lay the foundation of quality education is an important prerequisite for cultivating students' core quality. According to the relevant characteristics of students 'psychology, scientific educational activities and effective mental health education can not only better explore students' learning interest and passion, gradually build high-quality psychological quality, cultivate excellent communication skills, but also improve students' initiative and promote their healthy development. Therefore, current research aimed is to propose the integration and application of mental health education and foreign language teaching for sports school students, firstly, the current situation of mental health among students in sports schools and the problems existing in English classroom teaching are elaborated, and corresponding methods for integrating mental health education into English teaching in sports schools are proposed. A comprehensive analysis of the value of mental health education in the implementation of English courses in sports schools can effectively promote students in sports schools to better understand English, and improve psychological literacy in sports competitions during the learning stage. Studying the integration of English courses and mental health education can help cultivate students' strong psychological resilience and ability to overcome difficulties, laying a solid foundation for future employment and lifelong development. In addition, an integrated approach to enhancing mental health education and foreign language skills in sports school students can lead to improved overall well-being and language proficiency, fostering holistic development. The research limitations and future directions were also discussed that the end of study.